2020
DOI: 10.33197/jabe.vol6.iss1.2020.473
|View full text |Cite
|
Sign up to set email alerts
|

Peranan Keuangan Berkelanjutan Pada Industri Perbankan Dalam Mendukung Sustainable Development Goals

Abstract: The role of sustainable finance in the Banking Industry at this time was initiated by the Financial Services Authority (OJK) and World Wildlife Funding (WWF) in targeting economic growth so that negative impacts arise from the process of economic development. This encourages environmentalists, companies and national and global governments to trigger a sustainable development that prioritizes harmony in economic, environmental and social aspects. OJK has collaborated with financial institutions to develop a Sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 1 publication
0
2
0
3
Order By: Relevance
“…Lembaga jasa keuangan memiliki peranan yang penting dalam memacu pertumbuhan ekonomi namun sekaligus mengarahkan aktifitas berekonomi. OJK telah bekerjasama dengan beberapa lembaga terkait telah menyusun Roadmap Keuangan Berkelanjutan yang bertujuan untuk menjabarkan kondisi yang ingin dicapai terkait keuangan yang berkelanjutan di Indonesia dalam jangka menengah (2015-2019) dan panjang (2015)(2016)(2017)(2018)(2019)(2020)(2021)(2022)(2023)(2024) bagi industrijasa keuangan (Hayati, et al, 2020).…”
Section: A Pendahuluanunclassified
See 1 more Smart Citation
“…Lembaga jasa keuangan memiliki peranan yang penting dalam memacu pertumbuhan ekonomi namun sekaligus mengarahkan aktifitas berekonomi. OJK telah bekerjasama dengan beberapa lembaga terkait telah menyusun Roadmap Keuangan Berkelanjutan yang bertujuan untuk menjabarkan kondisi yang ingin dicapai terkait keuangan yang berkelanjutan di Indonesia dalam jangka menengah (2015-2019) dan panjang (2015)(2016)(2017)(2018)(2019)(2020)(2021)(2022)(2023)(2024) bagi industrijasa keuangan (Hayati, et al, 2020).…”
Section: A Pendahuluanunclassified
“…Dengan oleh sebab itu lembaga jasa keuangan dapat mengambil sikap untuk tidak membiayai perusahaan apapun yang tidak memiliki mitigasi risiko terhadap lingkungan. Sehingga kegiatan usaha berbasis lingkungan dapat berjalan sesuai dengan konsep kebijakan dan menjadi perusahaan yang berkelanjutan (Hayati, et. al.…”
Section: Regulasi Keuangan Berkelanjutan DI Indonesiaunclassified
“…There are several studies that have focused on exploring the evolution of green banking and sustainable finance, as well as identifying prospective research topics and areas for further study (Agustia et al, 2021;Andatu & Hilabi, 2023;Cahyaningtyas et al, 2023;Darma, 2022;Dewi & Sudarsono, 2021;Djajadiwangsa & Alversia, 2022;Gumantiny, 2022;Hayati et al, 2020;Kumajas et al, 2022;Malau & Rambe, 2022;Migliorelli, 2021;Yulia Nur Atriksa & Murwaningsari, 2022). In addition, researchers have examined investments in green banking, including green bonds, green insurance, and weather derivatives, while highlighting the determinants of green finance and the role of sustainable financial technology (Andatu & Hilabi, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a review of existing literature on green banking has identified important themes such as strategies to improve green banking, efforts to make green investments profitable, and challenges in green banking (Cahyaningtyas et al, 2023). These investigations also analyze the effects of green banking across diverse dimensions, encompassing the relevance of sustainability reporting, the impact of intellectual capital and financial competence on MSME sustainability, and the role of sustainable finance regulations in preparing taxpayers for carbon tax implementation (Agustia et al, 2021;Cahyaningtyas et al, 2023;Sudjono & Setiawan, 2022;Susanto et al, 2023) Moreover, they explore the significance of sustainable finance within the banking sector, particularly its alignment with the Sustainable Development Goals (SDGs), its sway on customer transaction preferences, and its efficacy within Islamic banking efficiency (Arraniri et al, 2020;Hayati et al, 2020;Metra et al, 2020). Additionally, investigations have delved into factors influencing tax evasion, profitability, and non-performing finances within manufacturing firms and Islamic Article's contents are provided on a Attribution-Non Commercial 4.0 Creative commons license.…”
Section: Introductionmentioning
confidence: 99%
“…These initiatives reflect an evolving development financing landscape that is increasingly shaped by interventions to create markets for sustainable finance, within Indonesia and elsewhere (Hayati et al, 2020;Mawdsley, 2018a). PT SMI, for example, positions itself as a 'market maker' and an 'ecosystem enabler,' where it works within an 'ecosystem' of regulators, project owners, donors and financiers in testing innovative financing solutions with an eye to finetuning policies and regulations and developing the 'right' financial/environmental market knowledge needed for sustainable finance to grow (Dalel, 2020).…”
Section: Introductionmentioning
confidence: 99%